Technopreneur Based Entrepreneurship Development Program as an Effort to Realize the Nationality of Nations in Politeknik Negeri Batam - Hati, Shinta Wahyu; Hidayat, Rahmat; Kartikaningdiyah, Ely; Gunawan, Hendra (Journal of Entrepreneurship, Business and Economics; Vol 6 No 2 (2018), 2019)
The Entrepreneurship Development Program (PPK) program is a place for students and alumnus in entrepreneurship. The Entrepreneurship Program implemented comes from the DRPM Ristek Dikti. The Entrepreneurship Development Program is a realization of the commitment of the Batam State Polytechnic in developing entrepreneurship. The Entrepreneurship Development Program at Batam State Polytechnic is an entrepreneurial program with the aim of producing new entrepreneurs who are independent based on science and technology. There is a series of activities in the process of recruiting tenants until the selection of candidates who have criteria has the right to participate in the program of entrepreneurship development. The method of implementing entrepreneurship development program activities through the Capacity Building with an approach in the context of empowering potential tenants using the PALS method (Participatory Action Learning System). The PALS method emphasizes the existing activities to be attempted to be brought to the condition of students through entrepreneurial awareness phase, capacity building and mentoring phase. The PALS method in the form of skills and management training is carried out with the aim of providing knowledge and understanding of entrepreneurship, encourage innovative ideas motivation, as well as to increase understanding in the management of business organization, the production of the operation, business financial, as well as making business and marketing business plan. The incubation activity in the Entrepreneurship Development Program received 41 candidates who were selected according to the criteria and then produced 25 tenants. At the end of the program the development of entrepreneurship has succeeded in producing new independent entrepreneurs who are ready to go to the community. Research paper Keywords: Science and technology, Entrepreneurship, Tenants, Capacity building, Business management, Skills Reference to this paper should be made as follows: Hati, S. W., Hidayat, R., Kartikaningdiyah, E., & Gunawan, H. (2018). Technopreneur Based Entrepreneurship Development Program as an Effort to Realize the Nationality of Nations in Politeknik Negeri Batam, Journal of Entrepreneurship, Business and Economics , 6 (2), 101–114.